Islands and international law - Rothwell, Donald R. (London [England] : Hart Publishing, 2022)
"Islands and their status in international law has become more of the more contentious issues in public international law. However, despite this, there is no rigorous book-length study on the question. This book fills that gap. Written by one of the world's leading public international lawyers, it offers an authoritative overview of how public international law operates in relation to islands. Key issues such as sovereignty, territorial rights, and governance are explored in depth. This will become a classic text in the field of international law."--
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily.
Mode of access: World Wide Web.
Keywords: Islands -- Law and legislation; Territorial waters; Electronic books